Annotated catalogue and bibliography of marine and estuarine shrimps, lobsters, crabs and their allies (Crustacea: Decapoda) of Argentina and Uruguay (Southwestern Atlantic Ocean) - Spivak, Eduardo Daniel; Farias, Nahuel Emiliano; Ocampo, Emiliano Hernan; Lovrich, Gustavo Alejandro; Luppi, Tomas Atilio
Twenty seven years ago, the ComisiónTécnica Mixta del Frente Marítimo publisheda catalogue of marine decapod andstomatopod crustaceans registered in coasts,continental shelf and slope, and deep waters ofArgentina (Boschi et al., 1992), that included 93species of decapods. Later, a list of decapods ofUruguay appeared with 107 marine and estuarinespecies (Zolessi and Philippi, 1995). Sincethen, the acknowledgement of the importanceof biodiversity for the human kind and the manyprocesses affecting it, such as the growing ratesof biological invasions and global climate change,make necessary to review previous knowledgeon local biodiversity. Moreover, the incresinguse of molecular techniques in taxonomic revisionshave unveiled the existence of misidentifications,cryptic species and species complexin numbers that significantly alter our previousconsiderations on species richness at the localand regional scales. The present catalogue includesthe addition and removal of species andan actualization of the published bibliographyrelated with them. The study area comprises estuariesand marine waters of the SouthwesternAtlantic Ocean in front of Uruguay and Argentina(33-60ºS), including the coasts, continentalshelf and slope, the contiguous abysal plains,the Malvinas, Georgias del Sur and Sandwich delSur Islands and the Scotia Sea. Fil: Spivak, Eduardo Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Farias, Nahuel Emiliano. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Ocampo, Emiliano Hernan. ...